PEMBANGUNAN KORIDOR EKONOMI SUMATERA BARAT SEBAGAI STRATEGI MEMPERKUAT KONEKTIFITAS DENGAN PEREKONOMIAN NEGARA ASEAN (JURNAL ECONOMICA : Research of Economic And Economic Education, 2016)
ABSTRACT The improvement of development economic  zone through economic corridor begins with the development of primary commodities which  have been increasing  household income. It followed by the development of basic infrastructure through the development of regional logistic and local transportation system.Then it continued with the development of regional innovation system through value-added primary products enhancement on the economic corridor zone. Development of economic corridors zone will support acceleration of economic growth. It also supported by  the development of connectivity within economic corridors in the province of West Sumatra. The development of the economic corridor connectivity is applied through  development of regional logistic systems(Sislogda), the development of regional transport systems (sistrada) and the establishment of exsport processing zones its support to ASEAN economic community on 2015. Keywords : economic corridor, economic connectivity with ASEAN ABSTRAKPengembangan zona pembangunan ekonomi melalui pembangunan koridor ekonomi dimulai dengan pengembangan komoditi utama yang selama ini mendorong pendapatan rumahtangga masyarakat, dilanjutkan dengan pengembangan infrastruktur dasar melalui pengembangan sistem logisitik daerah dan sistem trasportasi daerah, kemudian dilanjutkan dengan pengembangan peningkatan sistem inovasi daerah melalui peningkatan nilai tambah produk utama yang dihasilkan pada koridor ekonomi tersebut. Koridor ekonomi dengan tema pembangunan dan kegiatan ekonomi utamanya sebagai pemicu terjadinya percepatan pertumbuhan ekonomi, di dukung pula oleh strategi pengembangan konektifitas di dalam maupun antar koridor ekonomi yang ada di wilayah provinsi Sumatera Barat. Pengembangan konektifitas pada koridor ekonomi dilakukan melalui pengembangan sistem logistikdaerah (Sislogda) dan pengembangan sistem transportasi daerah (sistrada) dan pembentukan zona prosesing export, sebagai upaya menyambut pasar bebas ASEAN 2015. Keyword: Koridor ekonomi, Konektifitas Ekonomi dengan ASEAN